2018
DOI: 10.1136/bcr-2018-225281
|View full text |Cite
|
Sign up to set email alerts
|

Uncommon manifestation of leptospirosis: a diagnostic challenge

Abstract: Leptospirosis is a zoonotic disease commonly affecting the tropical countries. It may have protean clinical manifestations including hepatorenal dysfunction, myocarditis, pulmonary haemorrhage, meningitis, optic neuritis and rhabdomyolysis. Neurological manifestation of leptospirosis without the classical hepatorenal dysfunction is a rare entity. This complication of leptospirosis can present with diverse central and peripheral neurological presentations. The overlapping clinical manifestations with many commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Neurological manifestations can be seen in about 10–15% of patients with leptospirosis although signs of meningeal irritation occur in 80% of neuroleptospirosis cases [ 8 ]. According to Panicker et al [ 1 ], 40 patients admitted to a general medical ward over a 3-year period with acute neurological disease were found to have leptospirosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Neurological manifestations can be seen in about 10–15% of patients with leptospirosis although signs of meningeal irritation occur in 80% of neuroleptospirosis cases [ 8 ]. According to Panicker et al [ 1 ], 40 patients admitted to a general medical ward over a 3-year period with acute neurological disease were found to have leptospirosis.…”
Section: Discussionmentioning
confidence: 99%
“…Shermanii 2 Panicker, Mammachan and Jayakumar, 2001 [ 1 ] Primary neuroleptospirosis Fever, headache, and neck stiffness common serotypes implicated are Caninola, Icterohaemorragiae, and Pamona 3 Özdemir et al, 2008 [ 10 ] An discriminated aseptic meningitis case between rickettsia and leptospiral meningitis Fever, chills, rigors, headache, and disorientation Leptospira biflexa sv. Patoc 4 Bhatt et al, 2018 [ 8 ] Uncommon manifestation of leptospirosis: A diagnostic challenge Fever, diffuse dull-aching headache with generalized body aches and malaise. Worsening of sensorium in form of decreased responsiveness to commands, decreased verbal output and inability to move his limbs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A retrospective cross-sectional study in India found that among those presenting with acute neurological disease subsequently found to have leptospirosis, neurological manifestations usually manifest with signs and symptoms of aseptic meningitis, and are more commonly seen in the anicteric forms of leptospirosis 8. Encephalitis, transverse myelitis or Guillain-Barre syndrome, cerebellitis, or intracranial bleed may also occur in leptospirosis but are seldom seen 9. Radiological findings are variable.…”
Section: Discussionmentioning
confidence: 99%